2022
DOI: 10.1021/acs.jpcb.2c02990
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Cluster Formation in Aqueous Ethanol Solutions Probed by Soft X-ray Absorption Spectroscopy

Abstract: Hydrophobic cluster structures in aqueous ethanol solutions at different concentrations have been investigated by soft X-ray absorption spectroscopy (XAS). In the O K-edge XAS, we have found that hydrogen bond structures among water molecules are enhanced in the middle-concentration region by the hydrophobic interaction of the ethyl groups in ethanol. In the C K-edge XAS, the lower energy features arise from a transition from the terminal methyl C 1s electron to an unoccupied orbital of 3s Rydberg character, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…We note that in the case of methanol–water mixtures there is abundant data, also from X-ray spectroscopy, that indicates the presence of chains and cage-like structures; see ref . However, the different strengths of the hydrophobic interaction of the methyl and ethyl groups implicate some structural differences in the two systems, especially in the middle-concentration region …”
Section: Cmj-pes Studies Of Ethanol–water Mixtures In the Bulk Phase:...mentioning
confidence: 78%
See 1 more Smart Citation
“…We note that in the case of methanol–water mixtures there is abundant data, also from X-ray spectroscopy, that indicates the presence of chains and cage-like structures; see ref . However, the different strengths of the hydrophobic interaction of the methyl and ethyl groups implicate some structural differences in the two systems, especially in the middle-concentration region …”
Section: Cmj-pes Studies Of Ethanol–water Mixtures In the Bulk Phase:...mentioning
confidence: 78%
“…Several other techniques have been applied to ethanol–water and methanol–water mixtures, being relevant to the findings presented here, such as infrared spectroscopy, , NMR, , mass spectrometry, terahertz time-domain spectroscopy, X-ray and neutron diffraction experiments, NEXAFS, Compton scattering, and abundant molecular dynamics simulations; see ref . Many of these works have focused on explaining why the observed entropy increase upon mixing alcohol and water is much smaller than expected for an ideal solution.…”
Section: Cmj-pes Studies Of Ethanol–water Mixtures In the Bulk Phase:...mentioning
confidence: 99%
“…The self‐assembly behavior of ethanol‐water solutions is driven by hydrogen bonding between water as a proton donor and ethanol as a proton receptor under water ionization (Jiang et al, 2022), in which case, at higher initial ethanol concentration, a higher reinforcement will appear. Also, the hydrophobic interaction of the ethyl groups in ethanol molecules enhanced hydrogen bond structures in water (Nagasaka et al, 2022). Ågren et al (2022) showed that, at low concentrations, ethanol molecules form a film at the surface since ethanol at the surface can expose its hydrophobic part, while water at the surface cannot retain all its four possible hydrogen bonds.…”
Section: Resultsmentioning
confidence: 99%
“…35 This result means that an appropriate amount of ethanol denatures the proteins, causing them to unfold to a certain extent, exposing the hydrophobic groups, and thus enhance their surface hydrophobic properties. However, if the ethanol content exceeds a certain content (>30% v/v), they tend to form clusters due to the strong hydrophobic effect of the ethyl groups, 29 which may also interact with the hydrophobic groups on the surface of the proteins resulting in a lower number of hydrophobic groups measured. With the increase in heating time, the S 0 of the proteins in the 0 and 20% ethanol solutions first increased to a maximum (at 4 and 6 h respectively) and then decreased, while the S 0 of the proteins in the 50% ethanol solution increased slowly until 8 h and then decreased.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…27 As a commonly used solvent in the food and pharmaceutical industries, ethanol can alter the structure of proteins, thereby enhancing their biological and functional properties. 28 Ethanol molecules can interact with the water molecules, especially at high volume fractions, 29,30 change the dielectric constant of the aqueous solvent, and can denature the natural proteins by changing their conformational states. 31,32 Ethanol can also affect the fibrillation process and fibril morphology by changing the structure and properties of native proteins during denaturation, although the exact mechanism is still unknown.…”
Section: ■ Introductionmentioning
confidence: 99%